Phosphorus Dynamics in a Eutrophic Lagoon: Uptake and Utilization of Nutrient Pulses by Phytoplankton - Berthold, Maximilian; Schumann, Rhena (Frontiers in Marine Science, 2020)
Coastal ecosystems are subject to human impacts both through adjacent lands and by run-off from the broader catchment area. Nutrient inputs, like phosphorus, were often lowered decades ago, but many aquatic ecosystems have not recovered accordingly. Therefore, restoration and future protection measures need to be founded upon insights on the nutrient demands of phytoplankton in order to limit their growth and negative impacts upon coastal water bodies. This study investigated phosphatase activity, phosphate uptake, and growth of phytoplankton in a model lagoon system at the southern Baltic Sea coast. This lagoon system is perennially dominated by Cyanobium, a clade of picocyanobacteria which lack nitrogen fixation but which are common in brackish waters. Dissolved phosphate and total nutrient ratios from long-term monitoring point to an overall P-limitation of the system. Apparent phosphatase activities confirmed P-starvation. However, experimental phosphate-fertilisations repeated over an annual cycle increased chlorophyll concentration only when either dissolved nitrogen, or N-fixing cyanobacteria were present. In contrast to chlorophyll, particulate matter increased within a week most of the time at the observed stations, even in unfertilised samples. The difference between chlorophyll and particulate responses could be explained by chlorosis after phosphorus fertilisation, as nitrogen was co-limiting. Similar findings have been described for other water bodies. This study indicates that nitrogen is co-limiting in the lagoon system, and that phosphorus input has not yet declined sufficiently.